Approximate inverse for the common offset acquisition geometry in 2D seismic imaging*We gratefully acknowledge financial support by the Deutsche Forschungsgemeinschaft (DFG) through CRC 1173. Quinto additionally thanks the Otto Mønsteds Fond and U.S. National Science Foundation (under grants DMS 1311558 and DMS 1712207) for their support. He thanks colleagues at DTU and KIT for their warm hospitality while this research was being done. (12th December 2017) - Grathwohl, Christine; Kunstmann, Peer; Quinto, Eric Todd; Rieder, Andreas
Abstract: We explore how the concept of approximate inverse can be used and implemented to recover singularities in the sound speed from common offset measurements in two space dimensions. Numerical experiments demonstrate the performance of the method.